Assessment of factors affecting the sleep hygiene of medical students in Bahawalpur, Pakistan: a cross-sectional study - Zarafshan Shaﬁque (Brazilian Association of Sleep and Latin American Federation of Sleep Societies, 2021)
Objective: To identify the factors which have a statistically signiﬁcant association with sleep hygiene of medical students. Material and Methods: This study was done on 100 medical students. The questionnaire that was used for the collection of data had two parts. First was related to demographic variables and second was a validated Pittsburgh sleep quality index (PSQI). All participants were from the ﬁrst to ﬁfth years of Bachelor of Medicine and Bachelor of Surgery (MBBS). Data were analysed using SPSS 23. The association was found by applying chi-square test. Results: Our study revealed that out of 100 students, 61% had poor sleep hygiene (PSQI ≥ 5). Global PSQI scores among women were slightly higher than males. A statistical association was found between the residence and habit of studying at night of medical students with their sleep hygiene. Discussion: Medical students should ensure good sleep hygiene in order to maintain their academic performance, physical health, and mental health.